The crystal structure of 1,3(4,1)-dipyridin-1-iuma-2(1,8)-diethynylanthracena-5(1,3)-benzenacyclohexaphane-11,31-diium bis(hexafluoridophosphate), C36H24F12N2P2 - Hu Xia; Zeng Fei (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C36H24F12N2P2, triclinic, P1‾$\overline{1}$ (no. 2), a = 8.218(7) Å, b = 10.384(9) Å, c = 19.908(17) Å, α = 96.402(12)°, β = 91.216(12)°, γ = 101.161(12)°, V = 1655(2) Å3, Z = 2, Rgt(F) = 0.0685, wRref(F2) = 0.2188, T = 296(2) K.